Edukasi Penanganan Pertama Cedera Olahraga Pada Anggota PMR SMPN 5 Malang - Qonita Nabila; Dinda Permata Putri; Umbu Simon Payonga; Syarif Hidayatullah; Ika Niswatul Chamidah (Lembaga Pengembangan Kinerja Dosen, 2023)
Engaging in physical activities among adolescent students offers numerous benefits, one of which is the enhancement of brain function leading to improved cognitive abilities and focus during school learning. However, sports-related injuries are prevalent in school environments. Factors contributing to these injuries include inadequate warm-up, a lack of proper facilities, and high levels of physical activity. The higher the intensity of physical activity, the greater the risk of injuries. In school settings, the Youth Red Cross (PMR) plays a crucial role in providing basic medical assistance to individuals experiencing health issues. However, some PMR members lack proficiency in offering first aid for sports-related injuries. Therefore, it is essential to raise awareness about the correct and timely application of first aid in the event of sports injuries. This essay aims to discuss the importance of increasing understanding of first aid for sports injuries, with a specific focus on the PRICE method.